The conduciveness of the interior design of UP Engineering Library II for studying and reading as perceived by its users - Marco, Darrel Manuel O. (2009)
This study focused on the users' perception of the conduciveness of the interior design of the UP Engineering Library II for reading and studying. It utilized the descriptive research design.